Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran IPAS dengan Menggunakan Model Pembelajaran Project Based Learning (PjBL) di Kelas IV SDN 17 Pakan Kurai Kota Bukittinggi - Ramadhanty Rista Aida; Arwin Arwin (Universitas Pahlawan Tuanku Tambusai, 2023)
This research is based on the planning and implementation of IPAS learning which is still teacher centered, resulting in low learning outcomes of students in class IV SDN 17 Pakan Kurai Bukittinggi. This study aims to describe the increase in student learning outcome in IPAS learning using the Project Based Learning (PjBL) in class IV SDN 17 Pakan Kurai Bukittinggi City. The type of research is classroom action research using qualitative and quantitative approarches. The subjects of this research 26 students of class IV SDN 17 Pakan Kurai Bukittinggi City in the May, second semester of the 2022/2023 school year. The research procedure consists of planning, implementing, observing, and reflecting. The research data is in the form of qualitative and quantitative data. Data collection techniques used are observation, tests, and non-tests. The results showed: First, in the first cycle teaching module making obtained an average percentage of 87.48%(B), increased in cycle II to 95.83%(SB). Seconde, the result of the implementation of learning aspects of the teacher in cycle I obtained an average 79,68% (C), increased in cycle II to 93,75% (SB). Third, the result of the implementation of learning aspects of students in cycle I obtained an average 79,68% (C), increasing in cycle II to 93,75% (SB). Fourth, the learning outcomes of students in cycle I obtained an average 75,90 (C), increasing in cycle II to 85,97 (B). It can be concluded that the Project Based Learning model can improve student learning outcomes in learning IPAS in class IV SDN 17 Pakan Kurai Bukittinggi City.